Bentuk Dan Estetika Penyajian Musik Grup“Kesenian Sufi Multikultur” Di Kota Pekalongan - Fallah, Saiful; F, Totok Sumaryanto,; Wadiyo, Wadiyo (CV. ITTC INDONESIA, 2023)
“Multicultural Sufi Arts” group is a blend (acculturation) of religious art from Turkey that later was modified with local knowledge that it merges with religious art in Pekalongan. The statement of problem in this study are (1) How is the forms of music and dance presentations in the musical group of “Multicultural Sufi Arts” in the city of Pekalongan. (2) How is the aesthetic presentation of music and dance in the group of “Multicultural Sufi Arts” in the city of Pekalongan.This study uses an interdisciplinary approach with qualitative interpretative research design case study of social community or society, with the goal of understanding and describing the phenomenon of the form of music and dance presentations in the group of “Multicultural Sufi Arts” in the city of Pekalongan that is interpreted with aesthetics study. This study uses observation, interviews and document research in collecting the data. The validation technique of data is using triangulation of data sources and then analyzed using content analysis models.The result of the study shows the form of presentation of “Multicultural Sufi Arts” group are include: (1) Music, (2) Dancer, (3) Fashion-style, (4) Make up, (5) Lighting, (6) Room (stage), (7) Time (tempo and rhythm), and (9) Pronunciation (song or poem that is sung). Aesthetic presentation of “Multicultural Sufi Arts” group includes: (1) Sense (variety of sense), (2) Formal (various forms), (3) Associative (various associations), (4) Nature of form (creation of worship), (5) Contemplative-tracendental, (6) Symbolic and (7) Philosophical.Suggestions in this study, there is still a gap of “Multicultural Sufi Arts” group that it can be collaborated with modern music to make it more attractive and more acceptable to young people such as including religious pop songs and modern instruments in it, but remained consistent as the arts in the context of approach to the God.